Instantaneous frequency from Hilbert-Huang transformation of digital volume pulse as indicator of diabetes and arterial stiffness in upper-middle-aged subjects. Issue 1 (December 2018) - Wei, Hai-Cheng; Xiao, Ming-Xia; Chen, Hong-Yu; Li, Yun-Qin; Wu, Hsien-Tsai; Sun, Cheuk-Kwan
Abstract To investigate the value of decomposed short-time digital volume pulse (DVP) signals in discerning systemic vascular anomaly in diabetic patients, demographic and anthropometric parameters, serum lipid profile, fasting blood glucose and glycated hemoglobin (HbA1c) levels were obtained from 29 healthy adults (Group 1) and 29 age-matched type 2 diabetes mellitus patients (Group 2). Six-second DVP signals from right index finger acquired through photoplethysmography were decomposed using ensemble empirical mode decomposition. Using one intrinsic mode function (IMF5), stiffness index (SI) and instantaneous energy of maximal energy (fEmax ) were obtained. Other indicators of arterial stiffness, including electrocardiogram-pulse wave velocity of foot (ECG-PWVfoot ), crest time (CT) and crest time ratio (CTR), were obtained from the testing subjects for comparison. The mean body weight, body mass index, waist circumference, HbA1c and fasting blood sugar levels were higher in Group 2 than those in Group 1, whereas values of systolic and diastolic blood pressure were lower in Group 2 than those in Group 1. SI and fEmax were significantly higher in Group 2 than those in Group 1. Moreover, fEmax was positively associated with HbA1c concentration, CT and SI in Group 2 (p < 0.05) but not in Group 1. When all subjects were considered, fEmax was highly significantly associated with HbA1c and fasting blood sugar levels, and SI (allp < 0.001). After Hilbert-Huang transformation, short-time DVP signals could give significant information on arterial stiffness and vascular anomaly in diabetic patients.